Pigeonpea (Cajanus cajan L.) and Cowpea (Vigna unguiculata L.) Water as Alternative Growth Medium for Escherichia coli and Staphylococcus aureus in Laboratory with Minimum Infrastructure - Norma Kambuno; Ninda P. Y. Amtaran; Sherly Dewu; Kuntum E. Nurdin; Ni Made Susilawati; Yoan Novicadlitha (Universitas Nahdlatul Ulama Surabaya, 2021)
The availability of non-synthetic media from natural ingredients is needed to answer the needs in laboratories where the price of nutrient media is quite expensive and there are limited supplies of material ware houses. Cowpea (Vigna unguiculata L.) and pigeonpea (Cajanus cajan L.) are the local foods of people of NTT (East Nusa Tenggara) which have a high enough nutritional content which has the potential to be developed into cheap, easy and simple non-synthetic media in making. The purpose of this study was to determine whether the agar media contained nutrient from cowpea and pigeonpea water can be used as a alternative for nutrient agar for the growth of Escherchia coli and Staphylococcus aureus bacteria. This research is a true experiment with posttest-only control design. The growth rate of S. aureus bacteria on pigeonpea medium, cowpea medium, nutrient agar medium, were 164 CFU/mL (SD=3,13), 161 CFU/mL (SD=3,02) and 164 CFU/mL (SD=3,21), respectively. The average growth of E. coli on cowpea medium, pigeonpea medium, and nutrient agar control medium were 163 CFU/mL (SD=2,79), 167 CFU/mL (SD-2,63) and 164 CFU/mL (SD=2,75) respectively. Test results ANOVA between pigeonpea medium, cowpea medium and nutrient medium in order to obtain p value = 0.145 (p> 0.05) for the growth of E. coli bacteria and p value = 0.393 (p> 0.05) for growth S. aureus. It was concluded that there was no difference between the number of bacterial colonies of E. coli and S. aureus on three medium. The pigeonpea medium and cowpea can be used to grow and alternative nutrient agar in order to grow bacteria E. coli and S. aureus.